A note about the usage of the computational simulation in the undergraduate courses in the programs of electrical and biomedical engineering - Nieto Chaupis, Huber (2017)
Computational simulation has played a relevant role in basics sciences as physics, also in applied sciences and engineering. Despite of the fact that the simulation topics might be relevant, most of them are not explicitly proposed as an independent course. For example in physics program the simulation has been part of the cap stone project and last year courses. The idea fundamental of making a computational simulation is that of anticipating the expected results of experiments, or also to test theoretical formalisms by which is expected novel results. In this paper, we analyze the capabilities of the simulation in courses like antennas which is a course of third and fourth year of the program of electrical engineering. Indeed, we provide through one example that the combination of new theories and simulation can provide novel techniques applied to nanomedicine inside the program of biomedical engineering.